PENATAAN LINGKUNGAN PERMUKIMAN RAWAN BANJIR DENGAN PENDEKATAN PARTISIPATIF DI KAWASAN SUB URBAN KOTA MAKASSAR - Jayanti Mandasari Andi Munawarah Abduh; Jonathan Mawakaman Nifinluri; Alya Nafisa Kadar; Ummu Qalsum Putri Akhmad; St. Rahma Nurannisa (JURNAL PELITA KOTA, 2023)
According to Article 1 Paragraph 3 Chapter 1 General Provisions of Law of the Republic of Indonesia Number 1 of 2011 concerning Housing and Settlement Areas, a residential area is a living environment outside a protected area, either in the form of an urban area or a rural area, which functions as a residential or residential environment. and places of activities that support livelihoods and livelihoods. Many residential areas are found in the sub-urban areas of big cities in Indonesia, one of which is Makassar City, South Sulawesi Province. These residential areas generally consist of residential areas or residences, as well as infrastructure facilities to support the needs of community activities. Along with the development of community life in Makassar City, settlement problems arise which are caused by several factors, one of the most common is the flood disaster. According to the Head of BPPD Makassar, there are three worst flood points in Makassar City, one of which is Paccerakkang Sub-district. The area always experiences floods when the rainy season comes. One of the factors that cause frequent flooding in Paccerakang Sub-district is poor drainage quality, inadequate green space, poor arrangement of the residential environment, and the behavior of people who still litter, so that the area is no longer able to accommodate large amounts of water discharge. and become one of the flood-prone areas in Makassar City. After understanding the factors that cause the Paccerakkang Sub-district area to become a flood-prone area, it is hoped that it will be able to provide the right solution to fix flood-prone residential areas in order to increase the readiness of the environment and surrounding communities in dealing with flood disasters using a participatory approach that involves the community in the decision-making process of planning and development of the area. Keyword: flood-prone settlements; participatory approach; Paccerakkang Sub-district